Access to health services for problematic use of illegal psychoactive substances among natives and non-natives: a study in the metropolitan area of Bologna - Raimondo Maria Pavarin (Istituto Superiore di Sanità, 2014)
AIM: To estimate access to health services among subjects with problems due to the use of psychoactive substances among people born abroad (non-natives) and to draw comparisons with those born in Italy (natives) using several data sources. DESIGN Analysis of the new accesses for problematic use of illegal substances in the health services (hospital, emergency unit) and in the services dedicated to drug addicts (SERT) in the metropolitan area of Bologna in the period 2004/2011. RESULTS: No significant differences are recorded in regard to the substances used and the standardized incidence rate per 10 000 (natives males 10.72, females 3.93; non-native males 10.39, females 3.23). Among the non-natives, younger and with a higher percentage of females as compared with the Italians, there is a lower likelihood of access to the SERT. CONCLUSIONS: The data reported describe the complexity of a problem that ought to be carefully monitored in the territory